Frequency of Urethrocutaneous Fistula After Use of Autologous Platelet-Rich Plasma - Ghazi, Waqar Hameed (Biological and Clinical Sciences Research Journal, 2025)
Hypospadias is one of the most prevalent congenital anomalies of the male genitalia, and urethrocutaneous fistula (UCF) represents the most common postoperative complication following surgical correction. Platelet-rich fibrin (PRF), an autologous biomaterial rich in growth factors, has recently gained attention as a potential biological barrier to promote tissue regeneration and minimize surgical complications. Objective: To determine the frequency of urethrocutaneous fistula following hypospadias repair using autologous platelet-rich fibrin membrane. Methods: This descriptive case series was conducted at the Department of Pediatric Surgery, Services Hospital, Lahore, from 20th June 2019 to 19th December 2019. A total of 139 male patients aged 1 to 12 years undergoing primary hypospadias repair were included through non-probability consecutive sampling. Patients with prior hypospadias surgeries or other genitourinary anomalies were excluded. Intraoperatively, autologous PRF membranes were prepared from each patient’s venous blood and applied as an intermediate layer over the neourethra following urethroplasty. Patients were followed for three months to assess the development of urethrocutaneous fistula. Data were analyzed using SPSS version 20.0. Post-stratification chi-square test was applied to evaluate associations, with a p-value ≤ 0.05 considered statistically significant. Results: The mean age of patients was 6.59 ± 2.15 years. Distal penile hypospadias was the predominant type (66.91%), and tubularized incised plate (TIP) urethroplasty was the most frequently performed procedure (73.38%). Urethrocutaneous fistula developed in 11 patients, resulting in a complication rate of 7.91%. Conclusion: The use of autologous platelet-rich fibrin membrane as an adjunct in hypospadias repair is associated with a low incidence of urethrocutaneous fistula. PRF may serve as a beneficial, cost-effective biological scaffold to enhance wound healing and reduce postoperative complications.